Perception of Nuclear Security as a Barrier to Female Representation in Africa - Primerose Ruhukwa (International Journal of Nuclear Security, 2023)
Women are strongly underrepresented in the nuclear energy sector, particularly in the field of Nuclear security. Regardless of several government efforts to increase the number of women in this field, which include gender balance polices, education, and awareness campaigns, the nuclear security industry remains a male-dominated field. The reason why nuclear security is shunned by most women in Africa is because of an incorrect perception of what nuclear security is. When a lay person hears the term nuclear, the first thing that comes to mind is nuclear weapons, and many are quick to judge, saying that Africa does not have any nuclear materials, not realizing that nuclear is more than just nuclear bombs. In Africa, the term security is associated mostly with men who safeguard sensitive buildings and public areas. People think of security in terms of men carrying guns. The security profession is usually undermined because of the lack of opportunities and privileges for people doing these jobs. Also, the fact that few women already work in the nuclear security industry, particularly in top positions, makes this field automatically perceived as a male job. Many wrong perceptions exist about what nuclear security is, and many young women simply do not know about the various career opportunities that nuclear security has. This paper seeks to clarify the wrong perceptions and myths about what nuclear security entails, highlight challenges that are hindering women from taking nuclear security as a profession, and suggest ways to increase female representation in the nuclear security industry.
Keywords: Women; Perception; Underrepresentation; Barrier; Challenges; Policies